Treatment Failure with IVIG in a Case of Multisystem Inflammatory Syndrome in Children Managed by Tocilizumab - Zabeen, Fahmida; Hassan, M Quamrul; Nessa, Badrun; Khan, Sadia; Ferdouse, Jannatul (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2020; 36(2): 152-159